Study of impulses during a walkover backward on the balance beam in women gymnasts - Hars, M.; Holvoet, P.; Barbier, F.; Gillet, C.; Lepoutre, F.-X. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
In many sports activities, the performance requires a high level in the ability of the athlete to cope with impending loss of balance during different balance-threatening situations. This is especially evident for woman gymnast performing acrobatic skills on the beam where falls are reported as the major cause of large deduction of points during judgement (FIG 2002) and severe injuries (McAuley et al. 1987, Bak et al. 1994, Lohrer et Grupe 1997, Léglise 1997). The extremely reduced base of support (0.10m wide), its height above the ground level (1.20m) and the fact that acrobatic displacements require on this apparatus both foot standing and hand standing balances, are among the most important factors which determined the body`s balance vulnerability. This study investigated dynamic balance control on a gymnastic beam when performing acrobatic skills at ground level height and at competition height. We studied the walkover backward movement, fundamental element for all gymnasts (The body is bent backward, from an upright stance on one foot, the hands are placed on the floor, and the legs are arced one after the other over the hands to arrive on one foot). How did a woman gymnast product at different surface heights impulses to move on the beam while maintaining her whole body balance on a limited base of support, was the main question related to which this work attempted to answer. Methods An experimental balance beam including four force plates under each support (hand and foot) was used. The dynamic forces on each support were collected. Furthermore, the variable kinematics were recorded with the three dimensional video-metric system Vicon (version 612- eight video cameras). Force plates and video system were synchronized and data were collected at 120Hz. Two experimental conditions were created: low height beam condition (height: 20cm above ground level) and high height beam condition (height: 120cm above ground level). A group of expert female gymnasts (n=5) were recruited for this study. The group consisted of 5 females having experience in gymnastic at the national level. After an individual warm-up period in which the gymnasts got their bearings, for each of the two conditions, subjects realised a minimum of five walkovers backward. The best trials (perfect execution for the judge) for each condition were used in data analysis. For the study, the movement was divided in various phases differentiated by the type of support during the acrobatic skill (hand standing, foot standing). For each trial the impulses were calculated. The validation was realised from dynamics and kinematics data. Results We focused on the first phase of movement in which the gymnast begins from a single stance on one foot and bent backward to place the hands on the floor. With this expert population of gymnasts, the first results show a very low product of lateral impulse in all subjects, and that for the two realisation conditions. When comparing impulses under two conditions, as balance beam height increased, first results show that horizontal impulse is especially affected. On the other hand, it appears high standard deviation for vertical and horizontal impulse values. A tendance to higher vertical and horizontal impulse values is observed for some gymnasts in low height beam condition as in high height beam condition. This suggest different inter-subject strategies to move on the bam during the acrobatic skill. Discussion/Conclusion This protocol may enhance our understanding of dynamic balance control during walkover backward on the balance beam. The preliminary results suggest especially different inter-subject strategies for perform the walkover backard. To identify, distinguish and explain this different strategies use by gymnasts to adapt to the constraints imposed by the movement, it would be interesting to study the relation with different individual parameters (flexibility ...).